Prenatal diagnostic accuracy and epidemiology of congenital lung malformations: A retrospective review of cases in a tertiary referral center in northern Finland in 2010–2020 - Topias Puumalainen; Tuomas Kauppinen; Hilkka Nikkinen (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Our objective was to investigate the accuracy of prenatal diagnoses of congenital lung malformations (CLM) compared to postnatal diagnoses in a population in northern Finland and to estimate the birth prevalence of CLMs in the same population. Material and Methods A retrospective review of all CLM cases in a tertiary referral center, Oulu University Hospital, Finland, in 2010–2020. Data were collected from medical records. The final postnatal diagnosis was recorded as the pathologic‐anatomic diagnosis, if available, and otherwise as the postnatal radiologic diagnosis. Results Our case series comprises 37 CLM cases. The prenatal detection rate of CLMs was 100%. The prenatal diagnosis was congenital pulmonary airway malformation (CPAM) in 34/37 cases (92%). The accuracy of prenatal CLM diagnoses was 60% compared to postnatal radiologic diagnoses and 51% compared to final postnatal diagnoses. Relative frequencies of different diagnoses in postnatally confirmed CLM cases were CPAM 47% (16/34 cases), bronchopulmonary sequestration (BPS) 15% (5/34), hybrid CPAM/BPS 15% (5/34), congenital lobar overinflation (CLO) 15% (5/34), bronchial atresia 6% (2/34), and bronchogenic cyst 3% (1/34). Postnatally confirmed cases of CPAM were more likely to have a higher CPAM‐volume ratio at diagnosis (p = 0.002), a higher maximum CPAM‐volume ratio during pregnancy (p < 0.001), macrocystic appearance on ultrasonography (p = 0.026), and mediastinal shift (p < 0.001) compared with the rest of the cases in this study. The prevalence of all CLMs combined was 3.71 cases per 10 000 live births. The prevalences of CPAM, BPS, hybrid CPAM/BPS, and CLO were 1.69, 0.56, 0.56, and 0.56 cases per 10 000 live births, respectively. Conclusions We found that all CLMs were detected prenatally, but almost half of the prenatal diagnoses were inaccurate compared to postnatal diagnoses. Most lesions were diagnosed prenatally as CPAM, but postnatally many of them turned out to be BPS, hybrid CPAM/BPS, or CLO. Postnatally confirmed CPAM cases were more likely to have a high CPAM‐volume ratio, mediastinal shift, and macrocystic appearance on prenatal ultrasonography compared with other CLMs. The prevalence of CLMs is still relatively poorly documented, but we provide new estimates in Finland.